Multiphase Investigation Into Nursing Soft Skills Enrichment - Rulloda, Melanjo Lim; Aliswag, Emerson Galang (Journal of Neonatal Surgery, 2025)
Background: There exists a widely recognized shortage in the soft skills at the health sector, especially in the areas of communication, teamwork, critical thinking, and professionalism. The current study seeks to mitigate this kind of shortage by reviewing the literature that relates to the soft skills development, establishing an expert consensus, and developing an outcome-based education (OBE) enrichment framework for institutional nurses. The research adopts a systematic multiphase research design comprising three phases of primary interest. Phase 1 is an integrative literature review to determine and examine different approaches to developing soft skills in various disciplines. Phase 2 employs the Modified Delphi Method, wherein nursing specialists engage in two rounds of questionnaires to narrow down and confirm the most critical soft skills for nursing practice. Phase 3 involves the establishment of an OBE framework that organizes core approaches and learning outcomes to provide practical application within nursing education and clinical practice. The integrative review in Phase 1 highlighted 64 distinct soft skills development approaches that falls under 4 themes namely collaborative learning, experiential learning, reflective practices and technology-enhanced methods, all of which showed positive effects on soft skills development. In Phase 2, nurse experts sharpened and prioritized these methods, choosing 12 key strategies that are most flexible to apply in actual nursing practice. They are mentoring, reflective writing, debriefing, role-playing, case scenarios, problem-based learning (PBL), project-based learning (PjBL), role modelling, verbal feedback, preceptorship, group discussion, and team-based learning (TBL). Phase 3 built upon these results to create an OBE framework that includes the 12 validated strategies for developing nursing soft skills. Implementation of these strategies in a structured manner in nursing education and in practice is likely to significantly enhance healthcare delivery and patient care quality through better interpersonal, cognitive, and professional competencies. Result: The study employed a three-phase research design to create an Outcome-Based Education (OBE) model for the improvement of the soft skills in institutional nursing. Phase 1 is involved an integrative review of 82 studies that yielded 64 distinct methods of soft skills development, which were grouped into a Experiential Learning, Collaborative Learning, Technology-Enhanced Learning, and Reflective Practices. Phase 2 used a Modified Delphi Method to these approaches through agreement among the nurse experts, initially shortlisting them to 23, and then subsequently to 12 key approaches most of the appropriate for the institutional nursing. These approaches prioritized the communication, teamwork, critical thinking, and professionalism. In Phase 3, the final OBE framework was constructed to apply these 12 approaches in a systematic manner in the nursing education and practice, providing an evidence-based and structured approach to enrich the soft skills of the nurses. This model offers a useful roadmap for enhancing the nurses’ competencies, that eventually leads to an improved patient care quality and interprofessional collaboration. Conclusion: In this study, an evidence-based Outcome-Based Education (OBE) model was formulated to advance soft skills in educational nursing at the institutional level. Employing a multiphase research design, it identified and tested 12 strategies with an emphasis on communication, collaboration, critical thinking, and professionalism that play a crucial role in effective nursing practice. An integrative a synthesis of 82 studies to guaranteed these strategies and filled the gaps in soft skills development, and a two-round Delphi method to ensured expert agreement regarding to their relevance and applicability. Through the incorporation of the nursing educator and trainer input, the research offers curriculum guidelines aligned with a actual healthcare needs.